Comparative Analysis of Mechanistic and Correlative Models for Global and Bhutan-Specific Suitability of Parthenium Weed and Vulnerability of Agriculture in Bhutan - Sangay Dorji; Stephen Stewart; Asad Shabbir; Ali Bajwa; Ammar Aziz; Steve Adkins (Plants)
Parthenium weed (Parthenium hysterophorus L.) is one of the most noxious and fast-spreading invasive alien species, posing a major threat to ecosystems, agriculture, and public health worldwide. Mechanistic and correlative species distribution models are commonly employed to determine the potential habitat suitability of parthenium weed. However, a comparative analysis of these two approaches for parthenium weed is lacking, leaving a gap in understanding their relative effectiveness and ability to describe habitat suitability of parthenium weed. This study compared the mechanistic model CLIMEX with random forest (RF), the best-performing of a suite of correlative models. When compared against occurrence records and pseudo-absences, measured by area under the receiver operating characteristic curve, true skill statistic, sensitivity, and specificity, the results revealed higher performance of RF compared to CLIMEX. Globally, RF predicted 7 million km2 (2% of the total land mass) as suitable for parthenium weed, while CLIMEX predicted 20 million km2 (13%). Based on binary maps, RF and CLIMEX identified 67 and 20 countries as suitable, respectively. For Bhutan, globally trained RF predicted 8919 km2 (23% of the country’s total 38,394 km2) as currently suitable, with high suitability in the southern, west–central, central, and eastern districts, particularly along major highways. For the future, the 10 general circulation models downscaled to Bhutan showed a decrease in suitability across four scenarios (SSP126, SSP245, SSP370, SSP585) and three periods (2021–2050, 2051–2080, 2071–2100), with a northward shift in suitable habitats ranging from 2 to 76 km. Additionally, 2049 (23%) km2 of agricultural land is currently at risk of being invaded by parthenium weed. Correlative and mechanistic models are based on different niche concepts (i.e., realized and fundamental, respectively), and therefore combining them can provide a better understanding of actual and potential species distributions. Given the high suitability of parthenium weed under the current climate and its potential negative impacts in Bhutan, early action such as early detection and control of infested areas, regular survey and monitoring, and creating public awareness are proposed as risk mitigation strategies.